2010
DOI: 10.1016/j.medengphy.2010.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent fixation and implantation forces for a femoral knee component—An in vitro study

Abstract: Implant survival rate is a primary concern for individuals receiving a primary total knee arthroplasty. Loosening is the primary reason for revision surgery and was therefore the focus of the current study. To better understand the mechanics of implant fixation, the time-dependent fixation of a femoral knee component was measured in vitro on three cadaveric femurs. The fixation of each femoral knee component was measured with strain gauged implants for at least 10min on each femoral component. Additionally, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
0
9
1
Order By: Relevance
“…The average insertion force was a bit higher than reported by Burgers et al [15] who measured about 2500 N in their best bone quality case. We measured this range of insertion force only in the bones with BMD values lower than 150 mg/cm 3 , which means low bone quality.…”
Section: Effect Of Novel Surface Morphology On the Insertion Forcecontrasting
confidence: 61%
See 2 more Smart Citations
“…The average insertion force was a bit higher than reported by Burgers et al [15] who measured about 2500 N in their best bone quality case. We measured this range of insertion force only in the bones with BMD values lower than 150 mg/cm 3 , which means low bone quality.…”
Section: Effect Of Novel Surface Morphology On the Insertion Forcecontrasting
confidence: 61%
“…We measured this range of insertion force only in the bones with BMD values lower than 150 mg/cm 3 , which means low bone quality. Burgers et al [15] suggested that a horizontal impaction in their set-up could have caused a lower impaction force in their study. Moreover, we measured our insertion force during a gradual insertion instead of dynamic impaction; the latter probably being associated with increased peak forces.…”
Section: Effect Of Novel Surface Morphology On the Insertion Forcementioning
confidence: 77%
See 1 more Smart Citation
“…Relative to micromotion values reported in the literature, which were in the order of 0–250 µm, we found smaller ranges of micromotion . This is attributable to the fact that we did not model plasticity or visco‐elastic behavior of the bone, which are important factors for the primary stability of cementless implants . To include the effect of bone plasticity and the visco‐elastic effects on implant stability, future studies can focus on improving a more realistic continuum model of the mechanical behaviour of bone.…”
Section: Discussionmentioning
confidence: 71%
“…It has been shown that one of the critical factors that affect the seating stability of these taper junctions is the non-standardized assembly methods used to seat the femoral head onto the stem. 1–4 The seating of the head on the stem may depend on surgical, patient, and implant variables 1–4 that include visualization of the implant, patient size and age, and the nature of the implant being implanted. 1–4…”
Section: Introductionmentioning
confidence: 99%